Guidelines for Public Mind Characteristics Development of Students Under Kalasin Primary Educational Service Area Office 1 - Prasertsang, Wantanee; Duangchatom, Kritkanok (Journal of Education Rajabhat Maha Sarakham University, 2024)
The objectives of this research were 1) to study the current situation of public mind characteristics of the students and 2) to study guidelines for developing public mind characteristics of the students. The research was divided into 2 phases: Phase 1 studies the current situation of public mind characteristics of the students. The sample group consisted of 307 teachers on duty at the primary schools under the jurisdiction of the Kalasin Primary Educational Service Area Office 1. The sample size was determined using the Yamane’s formula to estimate the population proportion. The set proportion of the characteristics of interest in the population was 0.5 with 5 percent of acceptable error level and 95 percent of confidence level, drawn from stratified random sampling. The research tool was a questionnaire with 5 levels of rating scale. The data was analyzed by frequency distribution, percentage, mean and standard deviation. Phase 2 study guidelines for developing public mind characteristics of the students. The key informants were seven experts from purposive sampling. The semi structured interview was conducted in data collection and analyzed content of the interview data by interpreting and presenting them descriptively. The results of the research found that: 1) the current situation of public mind characteristics of the students under the jurisdiction of the Kalasin Primary Educational Service Area Office 1 in overall was at a high level and 2) the results of the guidelines study for developing public mind characteristics of the students under the jurisdiction of the Kalasin Primary Educational Service Area Office 1 consisted of 4 aspects including the aspect of practice or doing things for public interest found 5 development guidelines, the aspect of duties and self-responsibilities found 3 development guidelines, the aspect of sense of public responsibility found 6 development guidelines and the aspect of respecting the rights of others found 6 development guidelines. There were totaling 20 guidelines for developing public mind characteristics of the students under the jurisdiction of the Kalasin Primary Educational Service Area Office 1.